2013
DOI: 10.1158/1078-0432.ccr-12-1630
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Inhibition Is Associated with Enhanced Melanoma Antigen Expression and a More Favorable Tumor Microenvironment in Patients with Metastatic Melanoma

Abstract: Purpose: To evaluate the effects of BRAF inhibition on the tumor microenvironment in patients with metastatic melanoma.Experimental Design: Thirty-five biopsies were collected from 16 patients with metastatic melanoma pretreatment (day 0) and at 10 to 14 days after initiation of treatment with either BRAF inhibitor alone (vemurafenib) or BRAF þ MEK inhibition (dabrafenib þ trametinib) and were also taken at time of progression. Biopsies were analyzed for melanoma antigens, T-cell markers, and immunomodulatory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
793
5
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 845 publications
(855 citation statements)
references
References 23 publications
48
793
5
9
Order By: Relevance
“…In preclinical models and in patients, expression of MITF is upregulated following BRAF inhibition, with associated large-magnitude, although variable, increases in the expression of lineage antigens, such as gp100, melan-A, and tyrosinase-related proteins 1 and 2 (REFS 106,107). Whether increased expression of these antigens alone offers the opportunity for pre-existing tumourinfiltrating CD8 + T cells to recognize and contribute to the eliminaton of melanoma cells remains unknown; however, the observation that tumour-infiltrating lymphocyte counts are increased early in the course of BRAF-inhibitor therapy, when compared with those of tumour biopsy samples taken from the same patients immediately before therapy, supports this concept 107,108 . The characteristics of these lymphocytes have been described only preliminarily 109 , therefore, their contributions to therapeutic responses are unclear -markers of T-cell activation have been documented, but so have markers of T-cell exhaustion 104 .…”
Section: Talimogene Laherparepvec (T-vec)mentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical models and in patients, expression of MITF is upregulated following BRAF inhibition, with associated large-magnitude, although variable, increases in the expression of lineage antigens, such as gp100, melan-A, and tyrosinase-related proteins 1 and 2 (REFS 106,107). Whether increased expression of these antigens alone offers the opportunity for pre-existing tumourinfiltrating CD8 + T cells to recognize and contribute to the eliminaton of melanoma cells remains unknown; however, the observation that tumour-infiltrating lymphocyte counts are increased early in the course of BRAF-inhibitor therapy, when compared with those of tumour biopsy samples taken from the same patients immediately before therapy, supports this concept 107,108 . The characteristics of these lymphocytes have been described only preliminarily 109 , therefore, their contributions to therapeutic responses are unclear -markers of T-cell activation have been documented, but so have markers of T-cell exhaustion 104 .…”
Section: Talimogene Laherparepvec (T-vec)mentioning
confidence: 99%
“…These observations raised concerns that MEK inhibitors might not be a useful targeted-therapy backbone for combination immunotherapy, and that BRAF-MEK combination therapy might not be as capable of potentiating an immune response as BRAF-inhibition alone. However, increasing evidence from preclinical in vivo experience with MEK inhibitors 110 , and analyses of serial tumour-biopsy specimens from patients receiving combined BRAF-MEK-inhibitor therapy suggest a positive effect on the expression of MITF and melanocyte lineage antigens, and that T-cell infiltration persists under such treatment 107 . Moreover, a compelling additional observation indicates that MEK inhibitors can disrupt a deleterious signalling circuit between tumour cells and the so-called 'M2-like' macrophage population, which impair effector T-cell entry into tumours and drive melanomacell growth 111 .…”
Section: Talimogene Laherparepvec (T-vec)mentioning
confidence: 99%
“…Accumulating evidence has shown that mitogen-activated protein kinase (MAPK) inhibitors are capable of restraining the tumor growth and profoundly enhancing antitumor immunity in the following aspects 115 : (1) upregulate the antigen expressed on the tumor cells 116 ; (2) increase the numbers of tumor infiltrating CD8 þ cells 116,117 ; and (3) protect CTL from death by chronic TCR stimulation. 118 Current data showed that v-Raf murine sarcoma viral oncogene homolog B (BRAF) inhibitor-resistant tumor cells harbored an activated MAPK pathway and high expression of PD-L1.…”
Section: Combined With Targeted Therapymentioning
confidence: 99%
“…Molecularly targeted agents are also being combined with immune checkpoint inhibitors. BRAF inhibition, which is FDA-approved for the treatment of metastatic melanoma expressing the activating BRAF V600E mutation, has been shown to increase MHC expression, tumor antigen presentation, and T-cell infiltration (98)(99)(100)(101)(102). Similarly, MEK inhibitors have been shown to improve CD8+ T-cell activity in preclinical models in combination with PD-1 blockade (103).…”
Section: Future Directionsmentioning
confidence: 99%